2016
DOI: 10.3389/fpls.2016.01751
|View full text |Cite
|
Sign up to set email alerts
|

Linking Dynamic Phenotyping with Metabolite Analysis to Study Natural Variation in Drought Responses of Brachypodium distachyon

Abstract: Drought is an important environmental stress limiting the productivity of major crops worldwide. Understanding drought tolerance and possible mechanisms for improving drought resistance is therefore a prerequisite to develop drought-tolerant crops that produce significant yields with reduced amounts of water. Brachypodium distachyon (Brachypodium) is a key model species for cereals, forage grasses, and energy grasses. In this study, initial screening of a Brachypodium germplasm collection consisting of 138 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 64 publications
4
56
0
Order By: Relevance
“…Drought response has been investigated mainly in the diploid B. distachyon, given its emerging role as a plant model for temperate grasses (e.g. Luo et al, 2011;Verlest et al, 2013;Des Marais and Juenger, 2016;Fisher et al, 2016). However, the adaptive significance of natural variation observed in the drought physiology of this species complex is not well understood yet (but see Manzaneda et al, 2015;Des Marais et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought response has been investigated mainly in the diploid B. distachyon, given its emerging role as a plant model for temperate grasses (e.g. Luo et al, 2011;Verlest et al, 2013;Des Marais and Juenger, 2016;Fisher et al, 2016). However, the adaptive significance of natural variation observed in the drought physiology of this species complex is not well understood yet (but see Manzaneda et al, 2015;Des Marais et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While that previous study was limited to only two species of the complex, here we firstly deepen the study of the significance of trait divergence among the three species by analysing specific differentiation in leaf traits typically related to drought response (e.g. Fisher et al, 2016;Des Marais et al, 2017), such as water content, specific leaf area, electrolyte leakage, proline content and phytohormone content. Secondly, we analyse the differentiation of drought-tolerance-related traits between B. hybridum Iberian populations that are genetically distinct, and whether such phenotypic differentiation between B. hybridum populations is related to aridity.…”
Section: Introductionmentioning
confidence: 99%
“…Non-destructive imaging was shown to be an effective method for measuring drought response in plant. Plant area, estimated from images, is considered as a proxy for biomass and plant growth, and has been adopted to evaluate and quantify the plant response to drought stress (Honsdorf et al, 2014 ; Petrozza et al, 2014 ; Fisher et al, 2016 ; Malinowska et al, 2017 ). However, as organ occlusion becomes more pronounced (for instance, for many cereals including rice and wheat at the reproductive stages), the accuracy of projected plant area for estimating the biomass and plant growth decreases (Munns et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Optical imaging and computer-assisted feature extraction have the advantages of being non-destructive, potentially high-throughput and objective. They have been widely applied in phenotyping plant growth and development (Spalding and Miller, 2013 ; Duan et al, 2015 ; Montagnoli et al, 2016 ; Rebolledo et al, 2016 ), seeds (Duan et al, 2011 ), root systems (Lobet et al, 2017 ), plant disease symptoms (Mutka and Bart, 2014 ), and plant abiotic stress (Altamimi et al, 2016 ; Fisher et al, 2016 ; Malinowska et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, lines with stable yield traits could be used in future rice breeding programs. Phenotyping drought tolerance characteristics and association with metabolomics coupled with multivariate analysis have provided leads into understanding plant early response to drought and plant adaptation [234][235][236]. Identification of key mechanisms such as mobilization of carbohydrates to support aerial growth at the expense of the roots indicated that growth and biomass production are key phenotypic traits to observe for drought tolerance screening.…”
Section: Phenomics and Physiological Phenotypingmentioning
confidence: 99%